Legal Framework and Mechanism of Marine Fisheries Subsidies in the Aspects of International Trade and Sustainable Development - Yusuf, Adijaya; Ariadno, Melda Kamil; Afriansyah, Arie (UI Scholars Hub, 2015)
Issues in fisheries have been regulated in various international conventions. The United Nations Convention on the Law of the Sea 1982 (UNCLOS 1982) has builta regime in the field of conservation and management of fishery resources based upon maritime zones or fish species that exist and available in this zone. However, UNCLOS 1982 only focuses on the issue of fisheries in the Exclusive Economic Zone (EEZ) and the high seas, thus it was not sufficient to overcome the problems of high frequent of fishing in maritime zones which are fully subject to the jurisdiction of coastal states, such as in the Inland waters, archipelagic waters and the Territorial Sea. This article aims to examine the legal framework and mechanisms of fisheries subsidies in the aspects of trade and sustainable development. In this article, discussion would carried out in order to examine the legal framework and mechanisms of marine fisheries subsidies that are implemented with the principles of fair-trade and sustainable development, both in the international level, as well as in the national level. Thus, this research is expected to be able to bridge the interests of developed countries and developing countries, especially Indonesia, in order to achieve fair trade in the field of fisheries and resource utilization of sustainable fisheries.